New or little-known Diamesinae (Diptera: Chironomidae) from Oriental China - Sun, Bingjiao; Lin, Xiaolong; Wang, Xinhua; Makarchenko, Eugenyi A. (Zootaxa, 2019)
Morphological description for adult male of a new species Diamesa qiangi sp. nov. and redescription for adult males of the little-known species Linevitshia prima Makarchenko and Sasayusurika nigatana (Tokunaga) of subfamily Diamesinae from the Oriental Region of China are given.